Channel modeling and signal generation for ultra high density magnetic recording - Li, Yi Hu. (2010)
As the need of storage devices with higher capacity continues to increase rapidly, the hard disk with ultra-high recording density has to be desired and designed by alternative technologies. The Bit patterned media(BPM) technology leads to the new generation of hard disk. In order to modify and improve on this new technology, the simulation of the read-write process and the prediction of hard disks' performance become important issues in this research area. This project focuses on the BPM hard disk read-write process. The MATLAB based simulation programs are written to act as acid tests for verifying the viability of the BPM magnetic recording systems. Two simulators were designed in the project, one is the read head field distribution simulator and the other is the write process simulator. The proposed designs were able to plot the potential distribution of the read head; predict the write process failure rate and then calculate the read back signals. Other than numerical approach, mathematical approach was also involved to make the designs more efficient.